EFEKTIVITAS GOOGLE CLASSROOM DALAM PENGELOLAAN PEMBELAJARAN MASA PANDEMI DI SMA NEGERI 1 WONOSARI - Halimah Sa'diyah; Anisa Fitri Hastuti; Wibowo Heru Prasetiyo (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Teachers have been challenged to provide an adaptive and effective learning during the Covid-19 outbreak. This study aims to see the effectiveness of using Google Classroom in the impact of the disaster during the Covid-19 outbreak at SMA Negeri 1 Wonosari. This research is based on the power of Google Classroom in changing the learning process in the future into distance learning at SMA Negeri 1 Wonosari. The quantitative approach is used with surveys and interviews. Respondents in this study were 50 students and one civic education teacher. The results found that Google Classroom was effective as an online learning platform. Evidenced by 1) 64% of learning through Google Classroom is effective; 2) 68% of the delivery of the material is easy to apply; 3) 82% of the material is easily accessible; 4) 72% easy assignment delivery and; 5) 46% of students were satisfied with the material presented. To increase the effectiveness of using Google Classroom, the teacher may prepare well by providing information in advance. In addition, Google Classroom can be used not only for measurement, but also for learning and personal management.